1996
DOI: 10.1042/bj3130549
|View full text |Cite
|
Sign up to set email alerts
|

Spermine suppresses the activation of human neutrophil NADPH oxidase in cell-free and semi-recombinant systems

Abstract: Spermine, a cellular polyamine, down-regulates O2- generation in human neutrophils stimulated by receptor-linked agonist [Ogata, Tamura and Takeshita (1992) Biochem. Biophys. Res. Commun. 182, 20-26]. In this study, to elucidate the mechanism for the inhibition, the effect of spermine on cell-free activation of the O2- generating enzyme (NADPH oxidase) was examined. Spermine suppressed the SDS-induced activation of NADPH oxidase in a dose-dependent manner with an IC50 of 18 microM. The inhibition was specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
0
18
2
1
Order By: Relevance
“…These results strongly suggest that Spd acts as a cellular membrane protectant against chill-induced lipid peroxidation through prevention of superoxide-generating NADPH oxidase activation. Kitada et al (1979) and Ogata et al (1996) have observed that Spd and Spm inhibit NADPH oxidase activity in rat liver microsomes and human neutrophils, respectively. Kramer and Wang (1989) indicated that PAs could protect membrane lipids from chill-induced peroxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results strongly suggest that Spd acts as a cellular membrane protectant against chill-induced lipid peroxidation through prevention of superoxide-generating NADPH oxidase activation. Kitada et al (1979) and Ogata et al (1996) have observed that Spd and Spm inhibit NADPH oxidase activity in rat liver microsomes and human neutrophils, respectively. Kramer and Wang (1989) indicated that PAs could protect membrane lipids from chill-induced peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that PAs are capable of protecting membranes against ROSinduced lipid peroxidation (Kitada et al, 1979;Tadolini et al, 1984;Tadolini, 1988). Ogata et al (1996) recently found that PAs inhibited the activity of the superoxide-generating NADPH oxidases in human neutrophils. Their results provoked us to investigate the possible involvement of PAs in the chilling tolerance of cucumber cultivars.…”
mentioning
confidence: 99%
“…Von besonderem Interesse war die Identifizierung einer 14fachen Abnahme in der Expression von Ornithindekarboxylase, dem für die Produktion von Spermin und Spermidin verantwortlichen Antizym. Die ubiquitären Polyamine, welche in ihren höchsten Konzentrationen im Seminalplasma gefunden werden, sind Schlüs-selregulatoren der Spermatogenese [64] und Spermatidchromatinkondensation [65]; sie fungieren als Protektoren [66] und Radikalenfänger [67] der ROS. Interessanterweise verfügen sie auch über klar abgegrenzte AGE-Inhibitionseigenschaften, indem sie insbesondere Histone [68] schützen.…”
Section: Der Einfluss Des Dm Auf Die Spermatogeneseunclassified
“…The separation of neutrophils and the fractionation of PM were performed as previously described (24).…”
Section: Methodsmentioning
confidence: 99%